Association of body mass index with toxicity and survival in pediatric patients treated with cisplatin-containing regimens. (7th November 2020) - Bhandari, Rusha; Scott, Elizabeth; Yeh, Mei Yu; Wong, Kenneth; Rushing, Teresa; Huh, Winston; Orgel, Etan
Abstract: Malnutrition is associated with treatment-related toxicities (TRT) in adults with solid tumors and in children with leukemia. Few studies have assessed whether malnutrition in pediatric patients treated for solid tumors impacts risk for TRT, relapse, and/or survival. To address this knowledge gap, this retrospective study evaluated the association between body mass index (BMI) at diagnosis, and imputed BMI during therapy, on the prevalence of TRT, specific toxicities, relapse, and survival in pediatric patients with solid tumors treated with cisplatin-containing regimens. Kaplan–Meier curves and regression models evaluated the association between patient-specific characteristics (including BMI) and TRT, relapse, and survival. The cohort included 221 patients, of whom 22% were malnourished at diagnosis (10% were underweight and 12% were obese). Most patients (60%) experienced at least one severe TRT, and 30% developed more than one severe TRT. Most patients with obesity at diagnosis remained obese during therapy (62%). In multivariable analysis, obesity at diagnosis was significantly associated with a more than threefold greater risk for developing severe TRT (p = 0.037), specifically for acute or chronic kidney injury ( p = 0.014). Obesity at diagnosis and adolescent and young adult age (≥15 years at diagnosis) were associated with worse event-free survival (hazard ratio [HR] 2.32, p = 0.024 and HR 2.28, p = 0.010, respectively) and overall survival (HR 3.69, p = 0.006 and HR 2.6, p = 0.012, respectively). Obese and older patients therefore constitute populations at risk for poorer outcomes. Prospective studies are warranted to gain further insight into the mechanism and role of obesity and adolescence in developing TRT and/or treatment failure.